EFFECT OF SOCIAL ROLES ON GIRLS’ACADEMIC ACHIEVEMENT IN PUBLIC PRIMARY SCHOOLS IN KIPKOMO SUB COUNTY, KENYA - Riwongole, Patrick Kibet; Kirwok , Emily; Kikechi, Ronald Werunga (IJRDO - Journal of Social Science and Humanities Research, 2022)
Education despite facing several challenges has brought social order around the world, even in addressing the challenges of people, and in particular women and the disadvantaged. Increasing female education is a catalyst for bringing equality among the women and men as all of them are given equal opportunity to chase their dreams. The aim of the study was to assess the effect of social roles on girls’ academic achievement in public primary school in Kipkomo sub County, West Pokot County, Kenya. The study adopted a descriptive survey research design where both qualitative and quantitative data were collected. Data was collected through questionnaires for class teachers and teacher counsellors, and focused group discussions for girls in regular school and girls in rescue centres. The study targeted 1615 persons comprising of 1201 girls, 101 head teachers, 202 girls in rescue centres and 101 teachers counselors all public schools in Kipkomo Sub County. Using Krejcie and Morgan Table for determining sample sizes, the study used a sample size of 306 persons. Purposive sampling and proportion to size sampling techniques were used to arrive at the number of sampled persons per each category of the targeted group; hence 89 girls in regular schools, 101 academic masters teachers, 15 girls in rescue centres and 101 teacher counsellors. The data was analysed using descriptive and inferential statistics and presented in tables. The study established that girls are generally socialized into domestic roles such as care giving, cooking, cleaning and caring for other siblings and manual work with no focus on their schooling.  The study also revealed that most of the girls skip school to look after goats and calves in addition to considering themselves as the weaker sex and hence put less effort in their academics.